Death angel - Fairstein, Linda A. (New York : Dutton, 2013)
Discovering the body of a woman in Ramble urban park, New York Assistant DA Alex Cooper and Detective Mike Chapman uncover disturbing links between the savage crime and a string of cold-case disappearances. Is this enormous urban park a sanctuary in the middle of the city or is it a hunting ground for a killer with a twisted mind?
Keywords: Cooper, Alexandra -- (Fictitious character) -- Fiction; Public prosecutors -- New York (State) -- New York -- Fiction; Central Park (New York, N.Y.) -- Fiction; Detective and mystery fiction